ERIC recommendations for TP53 mutation analysis in chronic lymphocytic leukemia-2024 update - Malcikova, Jitka; Pavlova, Sarka; Baliakas, Panagiotis; Chatzikonstantinou, Thomas; Tausch, Eugen; Catherwood, Mark; Rossi, Davide; Soussi, Thierry; Tichy, Boris; Kater, Arnon P; Niemann, Carsten U; Davi, Frederic; et al. (Leukemia, 2024)
In chronic lymphocytic leukemia (CLL), analysis of TP53 aberrations (deletion and/or mutation) is a crucial part of treatment decision-making algorithms. Technological and treatment advances have resulted in the need for an update of the last recommendations for TP53 analysis in CLL, published by ERIC, the European Research Initiative on CLL, in 2018. Based on the current knowledge of the relevance of low-burden TP53-mutated clones, a specific variant allele frequency (VAF) cut-off for reporting TP53 mutations is no longer recommended, but instead, the need for thorough method validation by the reporting laboratory is emphasized. The result of TP53 analyses should always be interpreted within the context of available laboratory and clinical information, treatment indication, and therapeutic options. Methodological aspects of introducing next-generation sequencing (NGS) in routine practice are discussed with a focus on reliable detection of low-burden clones. Furthermore, potential interpretation challenges are presented, and a simplified algorithm for the classification of TP53 variants in CLL is provided, representing a consensus based on previously published guidelines. Finally, the reporting requirements are highlighted, including a template for clinical reports of TP53 aberrations. These recommendations are intended to assist diagnosticians in the correct assessment of TP53 mutation status, but also physicians in the appropriate understanding of the lab reports, thus decreasing the risk of misinterpretation and incorrect management of patients in routine practice whilst also leading to improved stratification of patients with CLL in clinical trials.
Keywords: nádorový supresorový protein p53; vysoce účinné nukleotidové sekvenování; DNA Mutational Analysis; chronická lymfatická leukemie; mutace; Mutation; Humans; Tumor Suppressor Protein p53; mutační analýza DNA; High-Throughput Nucleotide Sequencing; Leukemia, Lymphocytic, Chronic, B-Cell; lidé